Reed-Solomon Coded Cooperative Space-time Block Coded Spatial Modulation - Zhao, Chunli; Yang, Fengfan; Chen, Chen; Umar, Rahim (2021 International Conference on Wireless Communications and Smart Grid (ICWCSG), 2021)
A novel Reed-Solomon coded cooperative space-time block coded spatial modulation (RSCC-STBC-SM) scheme with two different RS codes is proposed. One RS code with smaller minimum distance is used at the source, but the other one with larger minimum distance is utilized at the relay. To effectively decode the source and relay RS codes, we propose the joint RS decoding algorithm at the destination. Simulation results show that the proposed RSCC-STBC-SM scheme outperforms the direct RS coded STBC-SM (RSC-STBC-SM) scheme. Moreover, our proposed RSCC-STBC-SM scheme also outperforms multiple existing schemes.